A Study of English Listening and Speaking Abilities and Cross-Cultural Understanding among Grade 10 Students Using the Drama-Based Teaching Method - Ponkhamkaew, Patipon; Phonnong, Isara (Ratchaphruek Journal, 2026)
This research is the study of English listening and speaking ability of Grade 10 students using drama-based teaching method. It aimed to: 1) Compare listening and English speaking abilities before and after using drama-based teaching method; 2) Compare English listening and speaking abilities after leaning with the 70 percent criterion; and 3) Compare Cross-Cultural understanding before and after using drama-based teaching method. The sample group were 40 students from Grade 10 of Bunluawittayanusorn school by cluster random sampling. The experimental instruments consisted of three lesson plans using drama-based teaching method each lasting four hours. The instruments for collecting data consisted of an English listening and speaking ability test, and a Cross-Cultural Understanding assessment. The data were statistically analyzed by percentage, mean, standard Deviation, and t-test. The results revealed : 1) Students had the English listening ability after learning higher than before learning, and English speaking ability after learning higher than before learning at a statistical significance level of .05; 2) Students had the English listening and speaking abilities after learning had higher than the 70 percent criterion at a statistical significance level of .05; 3) Students had the Cross-Cultural Understanding after learning higher than before learning at a statistical significance level of .05.